2012
DOI: 10.1128/aem.00035-12
|View full text |Cite
|
Sign up to set email alerts
|

Intraradical Dynamics of Two Coexisting Isolates of the Arbuscular Mycorrhizal Fungus Glomus intraradices Sensu Lato as Estimated by Real-Time PCR of Mitochondrial DNA

Abstract: bReal-time PCR in nuclear ribosomal DNA (nrDNA) is becoming a well-established tool for the quantification of arbuscular mycorrhizal (AM) fungi, but this genomic region does not allow the specific amplification of closely related genotypes. The large subunit of mitochondrial DNA (mtDNA) has a higher-resolution power, but mtDNA-based quantification has not been previously explored in AM fungi. We applied real-time PCR assays targeting the large subunit of mtDNA to monitor the DNA dynamics of two isolates of Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
(74 reference statements)
2
13
1
Order By: Relevance
“…The plateau level is a feature of microscopically determined root colonization dynamics after nonvital staining of all fungal structures. In contrast, vital staining and quantification of fungal nuclei based on nrDNA copy numbers often reveal a peak of fungal vitality after a few weeks of cultivation, followed by a decline (19,22,35,42). Assuming acceleration of the root colonization process by higher propagule levels, the negative abundance responses to intraspecific inoculation with G. intraradices and G. claroideum may in fact reflect shifts in colonization dynamics, with an earlier vitality peak and onset of the vitality decline, both occurring before the first harvest after 6 weeks of cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plateau level is a feature of microscopically determined root colonization dynamics after nonvital staining of all fungal structures. In contrast, vital staining and quantification of fungal nuclei based on nrDNA copy numbers often reveal a peak of fungal vitality after a few weeks of cultivation, followed by a decline (19,22,35,42). Assuming acceleration of the root colonization process by higher propagule levels, the negative abundance responses to intraspecific inoculation with G. intraradices and G. claroideum may in fact reflect shifts in colonization dynamics, with an earlier vitality peak and onset of the vitality decline, both occurring before the first harvest after 6 weeks of cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Two specific primer pairs were therefore developed, each amplifying only a part of the G. mosseae ribotypes, and applied as a duplex assay. For the G. intraradices isolate, previously designed primers (22) were used, as they were found suitable for the present study. The specificity of these qPCR assays was tested in silico using the Fast PCR software (28) as well as experimentally by cross-amplification experiments using different templates (plasmid standards, medic DNA extracted from roots and leaves, fungal DNA extracted from spores, and DNA extracted from medic roots colonized by each fungal isolate).…”
mentioning
confidence: 99%
“…Nevertheless, individual AMF species may differ in their effects on plant growth. The multiple occupancy of a single root fragment by AMF from different genera or species is now widely accepted (Alkan et al 2006;Reddy et al 2005;Van Tuinen et al 1998;Wagg et al 2011a), although this cooccupation is currently poorly understood (Alkan et al 2006;Krak et al 2012), and it remains unclear if the relationship is competitive, synergistic or antagonistic; indeed, their relationship may vary with plant hosts and/or environmental conditions (Wagg et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Kiers et al (2011) have suggested that individual AM species might use different strategies to supply resources and benefits to host plants when multiple AM species share an individual root system. The relationship between different AM fungal species, such as synergy, competition or antagonist and the effect of that relationship on a plant species is difficult to determine (Krak et al 2012), especially in karst habitats. Mixed inoculation was better than single inoculation for enhancing the plant traits for nutrient acquisition and biomass accumulation of B. papyrifera seedlings (Figure 1), which suggested that there could be a synergistic relationship among the AM fungi species.…”
Section: Effects Of Fungi Fungal Composition and Species On Plant Grmentioning
confidence: 99%